THE ROLE OF CRITICAL THINKING IN ENGLISH LANGUAGE CLASSROOMS - Artikova Makhim Turaboy qizi (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
This article examines the importance of widespread use in English lessons of activities that promote the development of critical thinking. As a result of the application of modern approaches and innovative methods, such as the development of critical thinking in English language teaching, students receive information about the development of logical thinking skills, fluency of speech, the formation of quick and correct response skills, stimulating enthusiasm for knowledge, as well as the importance of a creative approach in English lessons.